2007
DOI: 10.3758/bf03194108
|View full text |Cite
|
Sign up to set email alerts
|

Implicit memory influences the allocation of attention in visual cortex

Abstract: The visual environment is highly regular, with particular objects frequently appearing in specific locations. Previous studies of visual search have shown that people take advantage of such regularities, detecting targets more quickly when they appear at a predictable location within a given spatial configuration. Moreover, this effect depends on implicit rather than explicit memory for the configurations. These studies have suggested that implicit long-term memory for contextual information influences the all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
97
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(111 citation statements)
references
References 24 publications
14
97
0
Order By: Relevance
“…Although this view is compatible with our data, it has difficulty explaining previous eyetracking and ERP/MEG data in which repeated displays were associated with significantly fewer eye movements before the target was found (Peterson & Kramer, 2001;Tseng & Li, 2004;Zhao et al, 2012). In addition, the N2pc component of the ERP is greater for old than for new displays (Johnson et al, 2007;Schankin & Schubö, 2009). This component is known to index spatial attention rather than postperceptual decision and response (Luck & Hillyard, 1994).…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…Although this view is compatible with our data, it has difficulty explaining previous eyetracking and ERP/MEG data in which repeated displays were associated with significantly fewer eye movements before the target was found (Peterson & Kramer, 2001;Tseng & Li, 2004;Zhao et al, 2012). In addition, the N2pc component of the ERP is greater for old than for new displays (Johnson et al, 2007;Schankin & Schubö, 2009). This component is known to index spatial attention rather than postperceptual decision and response (Luck & Hillyard, 1994).…”
Section: Discussionsupporting
confidence: 44%
“…Similarly, scalp event-related potential (ERP) studies have reported a significantly greater N2pc component for repeated than for unrepeated displays approximately 200 ms after display onset (Johnson, Woodman, Braun, & Luck, 2007;Schankin & Schubö, 2009). Because N2pc is an index of spatial attention (Luck & Hillyard, 1994), these differences suggest that contextual cueing affects spatial attention relatively early.…”
mentioning
confidence: 99%
“…Primary visual cortex (V1 and V3 within the medial occipital lobes) as well as higher-level multimodal association areas receive inputs from both visual and auditory sensory systems. This neuroanatomic substrate provides the functional connectivity that supports implicit auditory-visual interactions, outside of conscious awareness, while at the same time supporting cognitive control (Banich & Compton, 2011;Johnson, Woodman, Braun, & Luck, 2007;Naatanen, Kujala, & Winkler, 2011;Salmi, Rinne, Degerman, & Alho, 2007). In fact, during the administration of the ''auditory'' digit span task, and most other ''auditory attention'' tasks, the medial occipital cortex is robustly activated (Gerton et al, 2004).…”
Section: Integrating Network Auditory-visual Interactions and Actimentioning
confidence: 94%
“…Targets are identified more effectively when they appear within repeated spatial configurations of distractors compared with novel contexts. Electrophysiological recordings during contextual cueing experiments have revealed modulation of targetselection mechanisms (Johnson et al, 2007;Chaumon et al, 2008Chaumon et al, , 2009Schubö, 2009, 2010;Telling et al, 2010), although findings have not been entirely consistent and studies have not always controlled adequately for eye movements. Furthermore, because the target appears embedded within distractors, it is not possible to test for perceptual modulations unambiguously.…”
Section: Introductionmentioning
confidence: 99%